Cultivating Mindful Learning in EFL Poetry Class: a Way to Make Creative and Productive Writers - Kadek Sonia Piscayanti (Universitas PGRI Semarang, 2021)
Cultivating mindful learning in the context of pandemic of covid-19 is a choice to stimulate creativity and productivity. In poetry class, mindful learning takes place in the creative process where creativity and productivity are focused on. This research aims at investigating how mindful learning can be cultivated to stimulate creativity and productivity of the students who took poetry course during the pandemic of covid-19 through online learning, particularly to know how the creative process happened. In the context of poetry course in English Language Education, mindful learning is implemented to grow the creativity and productivity in students’ poetry writing skills. This research is a qualitative research using critical narrative inquiry approach. The instruments used are observation sheet, mindful poetry journal and self-reflection. From the observation, mindful poetry journal and self-reflection it can be seen that students undergo a series of process that can cultivate their creativity and productivity. The findings show that there are many values found in students’ creative process that grows their creativity and productivity. The values found during the mindful practice are freedom to think, freedom to choose, freedom to express, freedom to decide, and freedom to reflect, that lead to creativity and productivity. It means that mindful learning has a big impact on the students’ creativity and productivity in writing poetry that they become creative and productive writers.